UJI AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL AKAR ENCOK (Plumbago zeylanica L.) TERHADAP PERTUMBUHAN Pseudomonas aeruginosa SECARA IN VITRO - nyoman mastra (Jurusan Analisis Kesehatan, Poltekkes Kemenkes Denpasar, 2019)
ABSTRACTBackground Pseudomonas aeruginosa is negative gram bacteria which cause urinary tract infection. Encok root contains tannins, alkaloids, saponins, tri-terpenoids and flavonoids. The purpose This purpose is to observe the antibacterial activities on encok root ethanol extract with various concentrations towards Pseudomonas aeruginosa bacteria growth. The Method The type of experiment used true experiment with posttest only control group design using Kirby-Bauer diffusion discs method on five concentrations (20%, 35%, 50%, 65% and 80%), work controls (Ciprofloxacin 5µg) and negatif control (96% ethanol). The result showed that the average diameter of inhibition zone of encok root ethanol extract at concentration 20% (10,5 mm), 35% ( 11,7 mm), 50% (11,8 mm) 65% (12,3 mm) and 80% (15,3 mm). These five concentration have medium until strong inhibition potential. Statistic analysis with One Way Anova the value of p(0,000)α(0,05). In Least Significant Difference test showed the significant different of inhibition zone in each extract concentration. Conclusion This examination showed that antibacterial activity of ethanol extract of encok root with various concentrations (20%, 35%, 50%, 65% and 80%) was difference in towards the growth of Pseudomonas aeruginosa bacteria.Keyword: Encok roots, antibacterial activity, Pseudomonas aeruginosa